2009
DOI: 10.1016/j.chom.2009.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 Induces Autophagy in Human Monocytes/Macrophages via Cathelicidin

Abstract: Autophagy and vitamin D3-mediated innate immunity have been shown to confer protection against infection with intracellular Mycobacterium tuberculosis. Here, we show that these two antimycobacterial defenses are physiologically linked via a regulatory function of human cathelicidin (hCAP-18/LL-37), a member of the cathelicidin family of antimicrobial proteins. We show that 1,25-dihydroxyvitamin D3 (1,25D3), the active form of vitamin D, induced autophagy in human monocytes via cathelicidin, which activated tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
652
4
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 703 publications
(692 citation statements)
references
References 45 publications
19
652
4
10
Order By: Relevance
“…7 Vitamin D exerts its effects on innate immune responses by the promotion of autophagy and the suppression of tissue remodeling and lung matrix breakdown. 8,9 A systematic review and meta-analysis on low serum vitamin D levels and tuberculosis in 2008 had included 7 studies with 531 participants and reported that low serum vitamin D levels were associated with a higher risk of active TB. 10 However,there is paucity of relevant epidemiological data regarding vitamin D deficiency in paediatric tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…7 Vitamin D exerts its effects on innate immune responses by the promotion of autophagy and the suppression of tissue remodeling and lung matrix breakdown. 8,9 A systematic review and meta-analysis on low serum vitamin D levels and tuberculosis in 2008 had included 7 studies with 531 participants and reported that low serum vitamin D levels were associated with a higher risk of active TB. 10 However,there is paucity of relevant epidemiological data regarding vitamin D deficiency in paediatric tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have linked vitamin D deficiency with an increased risk for susceptibility to active TB (Martineau et al ., 2007; Wejse et al ., 2007; Nnoaham and Clarke, 2008). The active form of vitamin D3 induces autophagy in primary human monocytes and THP‐1 macrophages via the expression of the anti‐microbial peptide cathelicidin, which activates transcription of the autophagy‐related genes encoding Beclin‐1 and ATG5 (Yuk et al ., 2009). In primary human macrophages and THP‐1 macrophages, active vitamin D3 also induces the localization of Mtb in autophagosomes in a cathelicidin‐dependent manner (Yuk et al ., 2009).…”
Section: Autophagy In the Immune Response To Tbmentioning
confidence: 99%
“…For example, in HBV (hepatitis B virus)-infected hepatocytes, the HBV x protein increases autophagy by up-regulating the expression of Beclin 1 [160]. In human monocytes and human myeloid leukemia cells, vitamin D3 has been shown to induce autophagy by up-regulating both Beclin 1 and Atg5 [161,162]. The transcription factor implicated has not been identified, but it has been shown that in human monocytes the effect of Vitamin D3 is mediated via cathelicidin.…”
Section: Nf-κbmentioning
confidence: 99%